National stories and narrative voice in the fiction of Joshua Ferris - Maxey, Ruth (Taylor & Francis, 2016)
In his début novel, Then We Came to the End (2007), Joshua Ferris narrates his story of a pre-9/11 Chicago advertising agency in the first-person plural. Such narrative experimentation recurs across his fiction and is often linked to national concerns. This essay analyzes narrative voice, personal pro- nouns, and the state of the nation, investigating a writer whose work has received much popular attention but little academic interest to date.